Performance Evaluation of Different Filter Media in Turbidity Removal from Water by Application of Modified Qualitative Indices - S Moalej; A Torabian; M Noori Sepehr; E Dehghanifard; G Badalians Gholikandi; A Dehnavi; AR Yari; AR Asgari (Tehran University of Medical Sciences, 2012)
Background: Water filtration units have been faced problems in water turbidity removal related to their media, which is determined by qualitative indices. Moreover, Current qualitative indices such as turbidity and escaping particle number could not precisely determine the efficiency of the media in water filtration, so defining new indices is essential. In this study, the efficiency of Anthracite-Silica and LECA-Silica media in turbidity removal were compared in different operating condition by using modified qualitative indices.Methods: The pilot consisted of a filter column (one meter depth) which consisted of a layer of LECA (450 mm depth) and a layer of Silica sand (350 mm depth. Turbidities of 10, 20, and 30 NTU, coagulant concentrations of 4, 8, and 12 ppm and filtration rates of 10, 15, and 20 m/h were considered as variables.Results: The LECA-Silica media is suitable media for water filtration. Averages of turbidity removal efficiencies in different condition for the LECA-Silica media were 85.8±5.37 percent in stable phase and 69.75±3.37 percent in whole operation phase, while the efficiency of total system were 98.31±0.63 and 94.49±2.97 percent, respectively.Conclusion: The LECA layer efficiency in turbidity removal was independent from filtration rates and due to its low head loss; LECA can be used as a proper medium for treatment plants. Results also showed that the particle index (PI) was a suitable index as a substitute for turbidity and EPN indices.